Electrohydrodynamic‐Induced SERS Immunoassay for Extensive Multiplexed Biomarker Sensing. Issue 9 (22nd December 2016) - Kamil Reza, Khondakar; Wang, Jing; Vaidyanathan, Ramanathan; Dey, Shuvashis; Wang, Yuling; Trau, Matt
Abstract : Cancer diagnosis and patient monitoring require sensitive and simultaneous measurement of multiple cancer biomarkers considering that single biomarker analysis present inadequate information on the underlying biological transformations. Thus, development of sensitive and selective assays for multiple biomarker detection might improve clinical diagnosis and expedite the treatment process. Herein, a microfluidic platform for the rapid, sensitive, and parallel detection of multiple cancer‐specific protein biomarkers from complex biological samples is presented. This approach utilizes alternating current electrohydrodynamic‐induced surface shear forces that provide exquisite control over fluid flow thereby enhancing target–sensor interactions and minimizing non‐specific binding. Further, the use of surface‐enhanced Raman scattering‐based spectral encoding with individual barcodes for different targets enables specific and simultaneous detection of captured protein biomarkers. Using this approach, the specific and sensitive detection of clinically relevant biomarkers including human epidermal growth factor receptor 2 (HER2); Mucin 1, cell surface associated (MUC1); epidermal growth factor receptor; and Mucin 16, cell surface associated (MUC16) at concentrations as low as 10 fg mL −1 in patient serum is demonstrated. Successful target detection from patient samples further demonstrates the potential of this current approach for the clinical diagnosis, which envisages a clinical translation for a rapid and sensitive appraisal of clinical samples in cancer diagnostics. Abstract : A simple, rapid, and specific immunoassay approach is developed using the combination of alternating current electrohydrodynamic fluid flow and surface‐enhanced Raman scattering‐based spectral encoding for the parallel measurement of multiple cancer biomarkers. The capability of this approach to simultaneously detect multiple serum biomarkers at concentrations as low as 10 fg mL −1 from patient samples is demonstrated.